2019
DOI: 10.3389/fmicb.2019.00255
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Contribution of the HtrA Protease and PDZ Domains to Its Function in Stress Resilience and Virulence of Bacillus anthracis

Abstract: Anthrax is a lethal disease caused by the Gram-positive spore-producing bacterium Bacillus anthracis . We previously demonstrated that disruption of htrA gene, encoding the chaperone/protease HtrA BA (High Temperature Requirement A of B. anthracis ) results in significant virulence attenuation, despite unaffected ability of Δ htrA strains (in which the htrA gene was deleted)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 70 publications
(137 reference statements)
1
23
0
Order By: Relevance
“…Multimers of LmHtrA could be detected at protein amounts higher than 1.25 μg protein, which were more pronounced in comparison to HpHtrA multimers. Additionally, a truncated and active version of recombinant HtrA (short HtrA, sHtrA) was detected, which has been also observed for autoprocessed HtrA from other bacterial species previously [18] (Fig. 3a, upper panel).…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Multimers of LmHtrA could be detected at protein amounts higher than 1.25 μg protein, which were more pronounced in comparison to HpHtrA multimers. Additionally, a truncated and active version of recombinant HtrA (short HtrA, sHtrA) was detected, which has been also observed for autoprocessed HtrA from other bacterial species previously [18] (Fig. 3a, upper panel).…”
Section: Resultssupporting
confidence: 80%
“…This appears to be in contrast to HtrA proteases expressed by Gram-positive bacteria. In Bacillus anthracis , N-terminal autoprocessing has been demonstrated as a requirement for both, secretion and activity [18]. Although it is not known whether truncated sHtrA from L. monocytogenes is the result of N-terminal or C-terminal cleavage, truncated LmHtrA is still caseinolytically active suggesting that L. monocytogenes also secretes HtrA into the environment as an active protease.…”
Section: Discussionmentioning
confidence: 99%
“…HtrAs are known to exhibit an additional chaperone‐like activity, which is independent of the proteolytic activity (reviewed in Skorko‐Glonek et al, 2013). In some cases (DegQ Ec , or Bacillus anthracis HtrA), the presence of PDZ domains is required for the efficient chaperone activity (Israeli et al, 2019; Malet et al, 2012). To the contrary, DegP Ec deprived of both PDZ domains retains its chaperone activity (Iwanczyk et al, 2007; Jiang et al, 2008; Jomaa et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Virulence-attenuating htrA gene disruption was implemented for the development of a live spore vaccine ( 5 7 ). Recently, we suggested that HtrA acts as both a protease/chaperone and a pleiotropic factor of gene expression ( 8 ). Here, we present transcriptome sequencing (RNA-seq) data sets describing the effect of htrA gene disruption on the global gene expression of B. anthracis in the presence/absence of H 2 O 2 .…”
Section: Announcementmentioning
confidence: 99%